A GHAZAL FROM THE COLLECTION (KULLIYAH) OF NAVOI IN THE FRENCH NATIONAL LIBRARY - Malikov, Akrom (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The following study analyses the ghazal on pages 9b-10a of the book "Gharayib al-sighar" in the collection of two volumes stored in the National Library of France in Paris with inventory numbers Turc 316 and Turc 317 of Alisher Navoi based on the contextual method. This ghazal is included in the 20th volume of Alisher Navoi’s collection of perfect works among the ghazals that are not included in the official books. The article’s novelty is that Navoi scholars have not yet analyzed or commented on this text. Moreover, the ghazal is studied based on the methodology of contextual analysis. The ghazal is considered as a part of the context of Alisher Navoi’s creativity, as an edge that shows the creative concept of Alisher Navoi, and it is emphasized that the metaphorical love praised in it is one of the core ideas of Sufism enlightenment. The text was researched directly using a facsimile electronic copy of Alisher Navoi’s collection, presented in the old Turkish alphabet, which was used by Alisher Navoi.